Sharing this walk: an ethnography of prison life and the PCC in Brazil - Biondi, Karina (Latin America in translation, 2016)
"The Primeiro Comando do Capital (PCC) is a São Paulo prison gang that since the 1990s has expanded into the most powerful criminal network in Brazil. ... During the period of Biondi's ... visits ... and her extensive fieldwork in prisons and on the streets of São Paulo, the PCC effectively controlled more than ninety percent of São Paulo's 147 prison facilities"--